Packing for Mars : the curious science of life in the void - Roach, Mary (W.W. Norton, 2010)
The author of Stiff and Bonk explores the irresistibly strange universe of space travel and life without gravity. Space is a world devoid of the things we need to live and thrive: air, gravity, hot showers, fresh produce, privacy, beer. Space exploration is in some ways an exploration of what it means to be human. How much can a person give up? How much weirdness can they take? What happens to you when you can't walk for a year? have sex? smell flowers? What happens if you vomit in your helmet during a space walk? Is it possible for the human body to survive a bailout at 17,000 miles per hour? To answer these questions, space agencies set up all manner of quizzical and startlingly bizarre space simulations. As the author discovers, it's possible to preview space without ever leaving Earth. From the space shuttle training toilet to a crash test of NASA's new space capsule (cadaver filling in for astronaut), she takes us on a surreally entertaining trip into the science of life in space and space on Earth.